Prelude to mass murder: the pogrom in Iași, Romania, June 29, 1941 and thereafter - Ancel, Jean; Seckbach, Fern (Yad Vashem, 2013)
Initiators, planners, and perpetrators -- Laying the groundwork for the pogrom -- Arrests, murders and robberies -- The great massacre -- The death trains -- The day after -- Târgu Frumos -- Roman -- Cǎlǎrași -- The death train to Podu Iloaiei -- Ancillary pograms -- The Iași Jewish community -- The Iași pogrom: The Romanian view